1977
DOI: 10.1203/00006450-197705000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Components of Monocyte and Neutrophil Chemotaxis in Cord Blood

Abstract: Rlonocyte and polynlorphonuclcar neutrophil (I'hlN) chemotaxis was studied in cord blood fro111 healthy terrn infants. Rlonocytc chemotaxis was nor~llal to increased ( 1 15-12670) whereas PRlN che~~lotaxis was clecreasecl (79%) in comp:lrison with that of healthy atlult control subjects. Generation of chenlotactic factors fro111 cord sera was inlpairecl, being 55% of that generated by pooletl nornlal hunlan serulll (I'NIIS). Cord serunl was less inhibitory than poolecl adult hurilan scrtrni for adult tilonocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
31
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 4 publications
6
31
0
Order By: Relevance
“…Neutrophils from neonates showed a decreased deformability (1) and a marked deficiency in movement toward different chemotactic stimuli (2)(3)(4)(5)(6). In addition generation of .…”
mentioning
confidence: 99%
“…Neutrophils from neonates showed a decreased deformability (1) and a marked deficiency in movement toward different chemotactic stimuli (2)(3)(4)(5)(6). In addition generation of .…”
mentioning
confidence: 99%
“…Previous observations have implicated abnormal membrane activity in neonatal PMNs. In addition to deficient chemotaxis (2,4,8), we have observed decreased deformability of neonatal PMNs (5). Mease et al (3) have demonstrated decreased phytohemagglutinin-induced aggregation of human PMNs.…”
Section: Discussionmentioning
confidence: 96%
“…Combined with decreased movement (2,4,8), decreased deformability ( S ) , and decreased lectin-induced aggregation of these cells (3), the data strongly point to a developmental functional PMN membrane abnormality. Whether this functional deficiency derives from a primary membrane defect or an indirect effect of submembranous elements upon the membrane remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chemotactic dysfunction of CBG has been clearly defined by many investigators (5,6,7,9,13,18). In CBG, response to varying concentrations of chemotactic factor, however, has not been examined, nor compared to ABG.…”
Section: Discussionmentioning
confidence: 99%